Mr. Klutz is nuts! - Gutman, Dan.; Paillot, Jim (New York : Scholastic, 2004)
A skateboarding principal offers unusual incentives to his students to motivate them to learn more.
School Library Journal
4.4
3-6
3-6
Keywords: Humorous stories; Learning -- Fiction; School principals -- Fiction; Schools -- Fiction; Humorous fiction; Learning and scholarship -- Fiction; School stories; School superintendents and principals -- Fiction